Building Leadership Ecosystem Towards Prosperous Indonesia - Suradika, Dharmaji; Winawan, Aga Adi; Istira, Geani Budiningsih (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Leadership is more than just a skill-set to direct and solve complex problems but also a way of transforming the life of a nation. The power of a leader can be seen from the impact of the people that he leads and the sustainability of the organization. A good leader is one that not only possesses the ability to transcend people to be and do better, but also positively influences them to use their power to contribute for a greater good. The role of a leader has become more evident during the time of crisis. Every decision creates multiple different outcomes and impacts. A leader must not only provide effective strategic moves, but also a safe-space to emotionally support the people he leads in overcoming the crisis. When a leader is absent or embodies poor leadership, the organization will not survive. Therefore, the power of a true leader lies within his own characters and the ability to navigate the crisis and transform it to the people that he leads. Understanding this importance of leadership has urged Pemimpin.id to navigate the values of inclusive, effective, and empowering leadership for a greater good and sustainable impact in Indonesia.